Dua Kronik Tionghoa dari Semarang dan Cirebon : Suatu Catatan tentang Asal Usul dan Kehandalan - Alexander Wain (Institut Kewarganegaraan Indonesia, 2025)
This article is the first comprehensive evaluation of the provenance and reliability of the two enigmatic Kronik Tionghua texts of Semarang and Cirebon (the ‘Malay Annals of Semarang and Cerbon’). Initially published by M.O. Parlindungan in 1964, historians have increasingly begun to use these documents when reconstructing Java’s early Islamic history. This article is a long overdue attempt to positively identify the Dutch colonial official (Cornelis Poortman) whom Parlindungan claims to have received the texts from. Although the article establishes that Parlindungan almost certainly knew this individual, discrepancies between his version of Poortman’s career and official Dutch records raise questions about whether Poortman could have found the two Kronik Tionghoa, at least in the manner described. The article then ends with a close textual analysis of both Kronik Tionghua which demonstrates the possibility that both texts were written by a modern, Dutch-educated author. The article therefore concludes that both texts are probable fabrications, albeit ones based on authentic texts.